Genome-Wide Identification of miRNAs in Oily Persimmon (Diospyros oleifera Cheng) and Their Functional Targets Associated with Proanthocyanidin Metabolism - Meng Zhang; Rong Wu; Xinlong Hu; Zhengrong Luo; Qinglin Zhang; Sichao Yang (Horticulturae)
Cultivated persimmon (Diosspyros kaki Thunb.) is a hexaploid (mostly) or a nonaploid with high heterozygosity, hindering molecular genetic studies on proanthocyanidin (PA) metabolism, which is a major trait for persimmon astringency. Recently, one of its wild diploid relative species, oily persimmon (Diospyros oleifera), has been assembled with a chromosome-level reference. Thus, oily persimmon is now regarded as a model plant for discovering new genes associated with PA metabolism, which is highly accumulated in the fruits of this genus. In our study, we identified genome-wide microRNAs (miRNAs) and their precursor sequence based on the chromosome-scale genome of oily persimmon and the miRNA database of “Eshi 1” according to the sequence alignment and secondary structure accession. The targets were predicted on the psRNATarget software based on the genome CDS database. The size, conservation, diversity, stem-loop hairpin structures, and genome location of miRNA or the precursor sequence were analyzed by bioinformatics tools. The promoter elements of the miRNA genes were predicted on the promoter-2.0 software, which indicated that the abundant cis-acting elements were light responsiveness, promoter, and enhancer regions. The qRT-PCR assay was performed to elucidate the potential expression patterns of precursor miRNA and their targets during fruit development, and one target gene, DkMYB22, of miR2911 was verified to promote the conversion of soluble tannins into insoluble tannins involved in the deastringency in persimmons. Together, this study provides a robust foundation for further functional verification of these miRNAs associated with the natural deastringency process in persimmon, thereby facilitating advancements in persimmon fruit breeding.